Salmonella Typhimurium ST313 isolated in Brazil revealed to be more invasive and inflammatory in murine colon compared to ST19 strains - Seribelli, Amanda Aparecida; Ribeiro, Tamara R. Machado [UNESP]; da Silva, Patrick [UNESP]; Martins, Isabela Mancini [UNESP]; Vilela, Felipe Pinheiro; Medeiros, Marta I. Cazentini; Peronni, Kamila Chagas; da Silva Junior, Wilson Araújo; Moreira, Cristiano Gallina [UNESP]; Falcão, Juliana Pfrimer (The Microbiological Society of Korea, 2021)
Salmonella Typhimurium (ST313) has caused an epidemic of invasive disease in sub-Saharan Africa and has been recently identified in Brazil. As the virulence of this ST is poorly understood, the present study aimed to (i) perform the RNA-seq in vitro of S. Typhimurium STm30 (ST313) grown in Luria-Bertani medium at 37°C; (ii) compare it with the RNA-seq of the S. Typhimurium SL1344 (ST19) and S. Typhimurium STm11 (ST19) strains under the same growing conditions; and (iii) examine the colonization capacity and expression of virulence genes and cytokines in murine colon. The STm30 (ST313) strain exhibited stronger virulence and was associated with a more inflammatory profile than the strains SL1344 (ST19) and STm11 (ST19), as demonstrated by transcriptome and in vivo assay. The expression levels of the hilA, sopD2, pipB, and ssaS virulence genes, other Salmonella pathogenicity islands SPI-1 and SPI-2 genes or effectors, and genes of the cytokines IL-1β, IFN-γ, TNF-α, IL-6, IL-17, IL-22, and IL-12 were increased during ST313 infection in C57BL/6J mice. In conclusion, S. Typhimurium STm30 (ST313) isolated from human feces in Brazil express higher levels of pathogenesis-related genes at 37°C and has stronger colonization and invasion capacity in murine colon due to its high expression levels of virulence genes, when compared with the S. Typhimurium SL1344 (ST19) and STm11 (ST19) strains. STm30 (ST313) also induces stronger expression of pro-inflammatory cytokines in this organ, suggesting that it causes more extensive tissue damage.
Keywords: cytokines; inflammation; invasion; RNA-seq; Salmonella Typhimurium ST313